Excessive early-life dietary exposure: a potential source of elevated brain iron and a risk factor for Parkinson’s disease - Dominic J Hare (Nature Portfolio, 2017)
Abstract Iron accumulates gradually in the ageing brain. In Parkinson’s disease, iron deposition within the substantia nigra is further increased, contributing to a heightened pro-oxidant environment in dopaminergic neurons. We hypothesise that individuals in high-income countries, where cereals and infant formulae have historically been fortified with iron, experience increased early-life iron exposure that predisposes them to age-related iron accumulation in the brain. Combined with genetic factors that limit iron regulatory capacity and/or dopamine metabolism, this may increase the risk of Parkinson’s diseases. We propose to (a) validate a retrospective biomarker of iron exposure in children; (b) translate this biomarker to adults; (c) integrate it with in vivo brain iron in Parkinson’s disease; and (d) longitudinally examine the relationships between early-life iron exposure and metabolism, brain iron deposition and Parkinson’s disease risk. This approach will provide empirical evidence to support therapeutically addressing brain iron deposition in Parkinson’s diseases and produce a potential biomarker of Parkinson’s disease risk in preclinical individuals.